Pengaruh Kesadaran dan Citra Destinasi terhadap Minat Kunjungan Telaga Madirda yang Dimediasi Persepsi Kualitas - Muhammad Alberta Erliyanto; Muzakar Isa (Jurnal Ilmu Manajemen, 2025)
The purpose of this study was to analyze the influence of destination awareness and destination image on the interest in visiting Telaga Madirda, with perceived quality as a mediating variable. The method used was a quantitative approach with a purposive sampling technique on 245 respondents who knew Telaga Madirda. Data were obtained through questionnaires and analyzed using the Partial Least Square (PLS) method through SmartPLS 3.0 software. The results of the study showed that destination awareness and destination image had a positive and significant effect on the perception of quality and interest in visiting. In addition, perceived quality was proven to mediate the relationship between destination awareness and destination image with interest in visiting. These findings indicate the importance of building awareness and a positive image of a destination and maintaining the quality of the tourism experience to increase tourist interest in visiting.